Pengaruh Jumlah Sinar Ultra Violet Terhadap Penurunan Kandungan Bahan Organik di Dalam Pengolahan Air Gambut yang Dilanjutkan dengan Saringan Pasir Lambat - M Ma’arij Harfadli (LPPM ITK, 2017)
One of the areas with a complicated drinking are the areas with peat soil. This area has a lot water source, one of treatments for peat water is variation in using the UV light for peat water processing.There is reactors in this research: the UV reactor is made of glass with a 6 liters of reactor volume. The reactor contains 15 watts of 3 ultra violet UV lamps. Processing raw water is done in batch and reactor continuously. The wavelength is 370 nm which initial absorbance value of 2.045. The optimum time occurs 30 minutes in 3 lamp of UV irradiation with the elimination of organic matters of 36 mg / l.73%.